Depth of focus and visual acuity with primary and secondary spherical aberration - Yi, Fan; Robert Iskander, D.; Collins, Michael (Vision research (Oxford), 2011)
► We estimate optimal combinations of spherical aberrations to extend depth of focus. ► We examine these combinations of wavefront in real eyes with adaptive optics. ► Spherical aberrations help to extend depth of focus while decreasing visual acuity. ► Primary or secondary spherical aberration alone is equally effective to extend DOF. ► Their combinations of different signs can extend DOF with a smaller loss of VA. It is known that the depth of focus (DOF) of the human eye can be affected by the higher order aberrations. We estimated the optimal combinations of primary and secondary Zernike spherical aberration to expand the DOF and evaluated their efficiency in real eyes using an adaptive optics system. The ratio between increased DOF and loss of visual acuity was used as the performance indicator. The results indicate that primary or secondary spherical aberration alone shows similar effectiveness in extending the DOF. However, combinations of primary and secondary spherical aberration with different signs provide better efficiency for expanding the DOF. This finding suggests that the optimal combinations of primary and secondary spherical aberration may be useful in the design of optical presbyopic corrections.